FEARURES AND PROBLEMS OF NATURAL HAZARDS INSURANCE MARKET - E. A. Tokareva (Vestnik MGIMO-Universiteta)
The article deals with characteristics and problems of world natural hazards insurance market. Special attention in this article is paid to activity of direct and indirect participants of the market: policy holders, insurance intermediaries, insurers, reinsurers, companies of construction industry and real estate, banks and other financial institutions, investors, rating agencies, Government. The article underlines the importance of adequate natural hazard risks assessment. The article describes factors that influence demand and supply aspects on the market. The supply is constrained by insurer’s and reinsurer’s capacity and the willingness of investors to finance natural hazard insurance market. Low interest of potential policy holders to buy natural hazard insurance is explained mainly by practice of post-disaster government relief programs. As insurance component increases in natural disaster compensation schemes, moral hazard decreases, but adverse selection goes up.